Synthesis and Surface Engineering of Inorganic Nanomaterials Based on Microfluidic Technology - Shen, Jie (Nanomaterials (Basel), 2020)
The controlled synthesis and surface engineering of inorganic nanomaterials hold great promise for the design of functional nanoparticles for a variety of applications, such as drug delivery, bioimaging, biosensing, and catalysis. However, owing to the inadequate and unstable mass/heat transfer, conventional bulk synthesis methods often result in the poor uniformity of nanoparticles, in terms of microstructure, morphology, and physicochemical properties. Microfluidic technologies with advantageous features, such as precise fluid control and rapid microscale mixing, have gathered the widespread attention of the research community for the fabrication and engineering of nanomaterials, which effectively overcome the aforementioned shortcomings of conventional bench methods. This review summarizes the latest research progress in the microfluidic fabrication of different types of inorganic nanomaterials, including silica, metal, metal oxides, metal organic frameworks, and quantum dots. In addition, the surface modification strategies of nonporous and porous inorganic nanoparticles based on microfluidic method are also introduced. We also provide the readers with an insight on the red blocks and prospects of microfluidic approaches, for designing the next generation of inorganic nanomaterials.